KEMAMPUAN KONEKSI MATEMATIS DALAM MENYELESAIKAN MASALAH MATEMATIKA - Aszahra, Zharla Zetira; Rosyadi, Alfiani Athma Putri; In’am, Akhsanul (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
Mathematical connection ability is one of the important mathematical skills for students to connect mathematical concepts with various contexts inside and outside mathematics. The purpose of this study was to describe the mathematical connection ability of students in class VIII B SMP Muhammadiyah 2 Batu based on high, medium, and low categories in solving mathematical problems. This research uses a qualitative approach with a descriptive type that will present the results of the analysis in the form of facts or conditions of the mathematical connection ability of students in class VIII SMP Muhammadiyah 2 Batu in solving mathematical problems. The data collection techniques used are documents, paired tests, and paired interviews so that this research will reveal how students solve math problems given in pairs. Data analysis techniques used include data collection, data condensation, data presentation, and conclusion drawing. The results of the analysis of this study found that high category subjects met 58.5%, medium category subjects met 41.6%, and low category subjects met 25% of the indicators of mathematical connection ability in solving mathematical problems. This study recommends further study of students' mathematical connection ability in solving mathematical problems both individually and collaboratively based on factors that influence students' mathematical abilities.